2011
DOI: 10.1038/leu.2011.387
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling strength regulates normal hematopoiesis and its deregulation is involved in leukemia development

Abstract: A strict balance between self-renewal and differentiation of hematopoietic stem cells (HSCs) is required in order to maintain homeostasis, as well as to efficiently respond to injury and infections. Numbers and fate decisions made by progenitors derived from HSC must also be carefully regulated to sustain large scale production of blood cells. The complex Wnt family of molecules generally is thought to be important to these processes, delivering critical signals to HSC and progenitors as they reside in special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
171
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(180 citation statements)
references
References 78 publications
(90 reference statements)
5
171
0
4
Order By: Relevance
“…This is achieved by down-regulation of key members in the destruction complex (APC/APC2). In contrast to TGFb, Wnt signaling is a positive regulator of self-renewal in HSCs and for megakaryopoiesis (Luis et al 2012;Macaulay et al 2013). When Wnt signaling is modestly enhanced, HSCs reconstitute better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is achieved by down-regulation of key members in the destruction complex (APC/APC2). In contrast to TGFb, Wnt signaling is a positive regulator of self-renewal in HSCs and for megakaryopoiesis (Luis et al 2012;Macaulay et al 2013). When Wnt signaling is modestly enhanced, HSCs reconstitute better.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt3a, one of 19 distinct Wnt ligands, has been reported to induce Wnt signaling in the hematopoietic system (Luis et al 2012). Similar to miR-99a;125b-2, supplementation with Wnt3a during megakaryocytic differentiation increased the total number of cells (Supplemental Fig.…”
mentioning
confidence: 99%
“…While there are conflicting data on the role of WNT signaling in normal hematopoietic stem cell self-renewal, mouse models have demonstrated that β-catenin is critical for AML stem cell self-renewal. [2][3][4] These data, combined with the clinical observation that increased canonical WNT signaling in AML blasts at diagnosis is associated with decreased rates of relapse-free and overall survival, suggested a potential clinical benefit for WNT suppression. 5,6 While this approach has shown promise in the treatment of AML, haematologica 2015; 100:e49 questions remain as to which subtypes of AML will benefit.…”
mentioning
confidence: 94%
“…In normal development Wnt activity is shortlived and expression of Wnt target genes oscillates, suggesting that Wnt activity is controlled by inherent negative feedback loops (8). Uncontrolled activation of the central effector of Wnt signaling, β-catenin, has been causatively linked to genome instability in multiple cancers, including hematopoietic malignancies (9)(10)(11)(12). However, how uncontrolled β-catenin promotes genomic instability in these malignancies is unknown.…”
mentioning
confidence: 99%